INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE VERSUS KINESIOTAPE ON UPPER TRAPEZIUS MYOFASCIAL TRIGGER POINTS A RANDOMIZED CLINICAL TRIAL (International Journal of Physiotherapy, 2018)
Background: This study was designed to inspect the effects of integrated neuromuscular inhibition technique (INIT) and kinesiotape (KT) on upper trapezius myofascial trigger points.Methods: Sixty subjects with active trigger points (53 females and seven males) were divided haphazardly into three equal groups. Group "A" received INIT three times/week while group "B" received KT twice per week for four weeks. Group "C" (control group) didn’t receive any treatment but follow instructions. Visual Analogue Scale (VAS), Arabic Neck disability index (ANDI) and cervical range of motion (CROM) were used to evaluate subjects at two intervals (pretreatment and post-treatment).Results: Statistical analysis shown that there was a significant change within-group of VAS, ANDI, side bending at both side pre-post treatment at groups A, B and C while (p0.05) while post-treatment there was a significant change in all variables as (p